The level of adoption knowledge management approach in the scientific supervision of scientific dissertations ( A study on a sample of faculty members in the College of Education at Tishreen University) - الشيخ, ساره (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to define the level of adoption knowledge management approach in supervision the scientific thesis by supervisors, and to achieve this goal, the descriptive approach was adopted, aqusestinnair desgined aimed to identify the level of adoption knowledge management five process: (Knowledge generation, knowledge storage, knowledge dissemination, knowledge application and use) by supervisors during their work in supervision the educational master thesis . The number of its phrases reached (75) statements, and they were applied to (26) academic supervisors from the College of Education at Tishreen University, and the studied variables included (training courses, number of years Experience in scientific supervision of master's theses). The results of the research showed that the level of supervisors ’adoption of knowledge management processes in scientific supervision of scientific theses was at a medium level with a relative importance of (64.75). It was also evident that there was no effect of and the follow-up of the training courses on the supervisors’ answers, while there was an effect of the years of experience in scientific supervision variable. And it was for (6 years and over).